2016
DOI: 10.4236/ajps.2016.73042
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Genetic Variability, Character Association and Path Co-Efficient Analysis on Morphological and Yield Attributing Characters of Taro [Colocasia esculenta (L.) Schott]

Abstract: The study investigated genotypic and phenotypic coefficients of variation, heritability, genetic advance at 5% selection intensity and in percentage of population mean of nine characters (plant height, leaf number, length and width of leaf lamina, number and weight of cormels per plant, weight of corm per plant, dry matter percentage in the tubers and tuber yield per from 14 cultivars of taro [Colocasia esculenta (L.) Schott]). Results indicated highest genotypic coefficient of variation for dry matter percent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 7 publications
2
10
0
Order By: Relevance
“…Similarly, petiole length, number of leaves per plant and leaf breadth conferred positive and significant correlation with leaf area at both the levels. These findings were consonance with Mohankumar et al, (1990), Thankamma et al, (1995 and Mukherjee et al, (2016). Highly significant positive correlation between herbage yield and number of leaves per plant might be assigned to more vegetative growth from the cormel of the colocasia genotypes.…”
Section: Fig1 Starch Content In Different Colocasia Genotypessupporting
confidence: 88%
“…Similarly, petiole length, number of leaves per plant and leaf breadth conferred positive and significant correlation with leaf area at both the levels. These findings were consonance with Mohankumar et al, (1990), Thankamma et al, (1995 and Mukherjee et al, (2016). Highly significant positive correlation between herbage yield and number of leaves per plant might be assigned to more vegetative growth from the cormel of the colocasia genotypes.…”
Section: Fig1 Starch Content In Different Colocasia Genotypessupporting
confidence: 88%
“…0.47 kg, 0.46 kg and 0.46 kg for 1 st year, 2 nd year and pooled data respectively (Table 5). It could be that increased leaf area, plant height and plant span observed in the best performing taro cultivars like Bor, Ahina and Makhuti intercepted more light leading to increased production of photosynthates effecting the food reserves in the corms and cormels and these corroborates findings of Pratiwi et al, (2014) and Mukherjee et al, (2016). The morphological characters like diameter and weight of corm and cormels also directly affected the yield, as cultivar Bor was recorded the highest corm and cormel diameter and weight.…”
Section: Yield Per Plantsupporting
confidence: 86%
“…Investigations have shown that colocasia contain digestible starch, protein of good quality, vitamin C, thiamine, riboflavin, niacin and high scores of proteins and essential amino acids. The crop is also very rich in dietary fibre, thus, it could be employed in the treatment of diseases such as obesity, diabetes, cancer and gastrointestinal disorders (Mukherjee et al, 2016). Taro is cultivated in an area of around 1.30 m ha with an annual production of 9.98 mt and average yield of 7.68 t/ha (FAOSTAT, 2016) and the major colocasia growing states are Assam, Nagaland, Manipur, Orissa, Maharashtra, Kerala, Andhra Pradesh, Meghalaya, West Bengal, Uttar Pradesh Gujarat, Tamil Nadu and Bihar.…”
Section: Introductionmentioning
confidence: 99%